Validity of Problem-Based E-Magazine on Human Digestive System for Primary School Science Learning - Nisak, Nikita Hoirun; Pritasari, Ade Cyntia (BASICA, 2025)
The aim of this research is to find out and describe students' difficulties in learning to read and write beginnings in class II at SDN Slarang 03. This research uses a qualitative descriptive approach using the case study method. This research data is the result of interviews with informants. Data comes from teachers, principals and class II students at SDN Slarang 03. Data is analyzed using techniques expressed as data reduction, data presentation and drawing conclusions. The research data was checked for validity using triangulation of techniques and sources. The results of this research show: (1) students' difficulties in beginning reading such as difficulty spelling letters into syllables, difficulty spelling syllables into words, difficulty distinguishing letters that are almost similar, (2) students' difficulties in learning to write is that there is no space between words, imperfect writing, taking a long time to write and, (3) the teacher's way of overcoming students' difficulties in learning to read and write initially, namely by using varied methods, changing seats, getting used to reading independently for 10 minutes, holding special study guidance for students who experience difficulties reading and writing, working together with parents in monitoring students' progress in reading and writing, providing ongoing practice for students who experience difficulties in reading and writing.